Environmental and epidemiologic determinants of hantavirus infection (hemorrhagic fever with renal syndrome) in the Podkarpacie – first epidemic in Poland in 2007-2008 – and endemic incidences of diseases - Knap, Józef Piotr; Nowakowska, Anna; Heyman, Paul; Burzyński, Waldemar; Rączka, Alicja; Dutkiewicz, Jacek; Lech, Jan; Brzostek, Teresa; Kornasiewicz, Renata; Bentkowski, Wacław; Litarska, Urszula; Witas, Małgorzata; et al. (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">These researches presented epidemiological and environmental conditions of cases of haemorrhagic fever with renal syndrome (HFRS) — a zoonoses caused by hantaviruses which were found for the first time in Poland in 2004 in the Sub Carpathian (voivodhship) and an epidemic of which occurred in 2007. Virological diagnostics and clinical courses of diseases, prophylactic and educational actions taken in the area and their effectiveness were discussed.